The Elements Analysis of Community Satisfaction Survey in Improving Health Services in the Regional General Hospital of Farmers and Fishermen of Boalemo Regency (Jurnal Ilmu Manajemen dan Bisnis, 2023)
The present study aims to 1) identify and analyze the elements of the community satisfaction survey in improving health services at the Farmers and Fishermen's Regional General Hospital, Boalemo Regency; 2) determine and analyze the factors that determine the success of the community satisfaction survey element in improving health services at the General Hospital of Farmers and Fishermen, Boalemo Regency.This study uses a qualitative approach with a descriptive type of research. The data collection techniques have been conducted through observation, interviews, documentation, and literature study.The results show that 1) Community Satisfaction in Improving Health Services at the Farmers and Fishermen Hospital of Boalemo Regency that the requirements, system mechanisms, and service procedures are in accordance with applicable regulations but related to completion time, the level of patient satisfaction is still low; 2) The factors that determine community satisfaction in improving health services at the Boalemo District General Hospital for Farmers and Fishermen are product quality, service quality, emotionality, price/tariff, and cost.
Keywords: Survey, Satisfaction, Health Services